A meta-analysis of the associations between the SLC6A4 promoter polymorphism (5HTTLPR) and the risk for alcohol dependence. (April 2015) - Villalba, Karina; Attonito, Jennifer; Mendy, Angelico; Devieux, Jessy G.; Gasana, Janvier; Dorak, Tevfik M.
Abstract : Serotonin reuptake variation is linked to a functional polymorphism in the promoter region of the SLC6A4 gene on chromosome 17. It is plausible that variations in genetically determined SLC6A4 activity may modify the risk for alcohol dependence. To determine whether this allele is associated with alcohol dependence, the authors conducted a systematic review and meta-analysis. Twenty-five studies including 8885 participants were reviewed and analyzed. The meta-analysis was carried out using a random-effects model. Overall, the results did not support an association between alcohol dependence and the SLC6A4 promoter polymorphism for the dominant, recessive, and additive genetic risk models, respectively [odds ratio (OR)=0.99 (95% confidence interval (CI): 0.83, 1.18), OR=0.86 (95% CI: 0.71, 1.03), and OR=0.88 (95% CI: 0.69, 1.13)]. When effect modification was tested for sex, race/ethnicity, presence/absence of a psychiatric disorder, year of publication, and diagnostic criteria, none of the factors were found to be significantly associated with alcohol dependence. The findings in this meta-analysis suggest that the SLC6A4 promoter polymorphism is not associated with alcohol dependence.